Ontology - based metabolic pathway prediction using saccharomyces cerevusiae data from genbank, ecocyc and kegg [compact disc] - 366186 Yuslina Zakaria (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2006